Нові знахідки трипільської антропоморфної пластики з реалістичними рисами - Овчинников, Е.В.; Квітницький, М.В. (Археологія, 2002)
Стаття репрезентує нові знахідки трипільської антропоморфної пластики. В статье публикуются новые находки трипольской пластики с реалистическими чертами из поселений Поросского региона и Каневщины, а также Побужья. Наиболее ранняя статуэтка (Полонистое), по всей видимости, налеп на кухонном сосуде, изображает женщину в шейном ожерелье. Остальные фигурки, вылепленные из типичной для трипольской пластики отмученной глины, изображают женщину преклонного возраста (Вильшана I), мужчину (Квитки II), женщину или молодого мужчину (хут. Хмельная). Для большинства статуэток характерная поза — лицо, обращенное к небу. Публикуемые головки отражают сочетание различных антропологических типов, что неоднократно отмечали исследователи Триполья. Несмотря на то, что в немногочисленных краниологических материалах не было обнаружено признаков арменоидов, можно предположить, что трипольские статуэтки с реалистически проработанными головками отражают присутствие последних в среде древнейших земледельцев лесостепной полосы Правобережной Украины. The new finds of figurines with realistic features of Tripolye culture are published in the proposed paper. These finds are coming from settlements of River Ros’, Kanev region, and the Bug River territory. The earliest figurine (Poloniste) which has been made of clay paste on the kitchen vessel as a fragment of modeled surface, represents the woman with a necklace. Other figurines, sculptured of typical Tripolian plastic elutriated clay, represent a woman of declining age (Vil’shana 1), a man (Kvitki II), a woman or a young man (Khmel’naya steading). Characteristic pose — face looking to heaven — is common for the majority of figurines. The published heads witness the presence of two morphological types of images corresponding to two anthropological types, namely Armenoide and Mediterranean. Experts on Tripolye repeatedly stress this fact. Despite the absence of Armenoide traits among not numerous available craniological materials, it is possible to assume that Tripolian statuettes with realistically worked heads reflect the presence of these people among the first cultivators of the Wooden Steppe zone of the Right Bank of the Dnieper River territory of Ukraine.